Unprotected Sex and Adolescents: Risk and Protection Factors - Miria Benincasa; Manuel Morgado Rezende; Janaína Coniaric (Psicologia, 2008)
The pregnancy is the first cause of internments (66%) in young women with age of 10 the 19 years in net SUS and the AIDS has been responsible for the potential years of lost life between young. In this study, one searched to identify the perception of this risk between adolescents in relation to AIDS and the risk factors related to sexual practice without protection. For this, one selected 32 adolescents, distributed in two pertaining groups to the classroom and the two to Classroom D, as specifications of the Abep. The method used for collection and analysis of data was the Focal Group. The pointed results as cause of this practical demonstrated little chance for this practice and restricted use of the protection information that had. The told consequences had been HIV/DST and precocious pregnancy. The presented factors of protection involved to prevent the sex and to select partners.